STUDENTS’ PERCEPTIONS IN TEACHING PARAGRAPH WRITING MATERIALS BASED ON EGRA TECHNIQUE - Jumiaty, Andi Asri; Atmowardoyo, Haryanto; Salija, Kisman (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
Paragraph writing is one of subject of study at university level but there are no books provide to teach this subject. Therefore, the researcher construct teh material for Pargraph Writing based on EGRA Technique. This research is to find out the students’ perceptions on paragraph writing material based on EGRA technique. The researcher applied the descriptive qualitative research. This research was conducted in English Education Department, Faculty of Education and Teacher Training of Muhammadiyah University of Makassar. The subjects of the research were the fourth semester students in academic year of 2018/2019. The questionnaires were given to the students as the instrument to find out the students’ perception on paragraph writing materials. The are several questions that are filled out by the students. The result of the students’ perception on the final draft of instructional paragraph writing materials based on EGRA technique was positive